Strengthening Zakat and Waqf Institutions for The Development of MSMEs in Nigeria - Adamu Abubakar Muhammad; Ibrahim Dahiru Idriss; Anas Adam Muhammad; Musa Ibrahim; Asma’u Muhammad Sa’ad (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
The goal of this study is to determine how Islamic finance mechanisms like Zakat and Waqf have influenced the growth of micro, small, and medium enterprises (MSMEs) in Nigeria. Today, both developed and developing nations recognized the significant contributions MSMEs made to their economies, their populations' social and economic advancement, and the stabilization of security measures. Due to the collapse of the international oil market and Nigeria's economic slump, real efforts to establish MSMEs have made a significant contribution to lowering unemployment rates, creating wealth, and reducing poverty among the populace in Nigeria. To establish long-term alternative methods of financing the MSMEs for their sustainable development in Nigeria, the impact of Islamic finance models of Zakat and Waqf are recognized on the growth of micro and small businesses even though they are still not widely used in Nigeria as tools for business development despite their applicability according to Islamic shariah. In order to collect data for the study, a qualitative methodology was employed through Primary sources that include a survey of pertinent literature, and secondary sources that include interviews with pertinent participants who had varied viewpoints on the topic. The research supported the claim that the growth of MSMEs using Islamic finance models of Zakat and Waqf points in the right direction for MSMEs’ promotion and development in Nigeria. The research also suggests using the Zakat and Waqf funds as part of a new plan to work with both internal and foreign investors to develop models and methods of funding MSMEs that are more successful, reduce the rate of poverty and unemployment in Nigeria, and it can be relevant to all regions throughout the world.